Textual reading of issues in Arabic grammar - Shyaa, Dr. Ali Razzaq (Thi Qar Arts Journal, 2023)
Textual modernists developed concepts, terminology, and standards for understanding and reading any text, seeking to make texts subject to the concepts, standards, and terminology they established - regardless of the size and nature of the text - but textualists were attracted by the text as a comprehensive structure more than they were attracted by the sentence, so studies on literary texts and their analysis began in In light of what textual science has brought, most studies have dealt with Qur’anic, poetic, and narrative texts. To show the disparity between texts and highlight their impact on the recipient, our research, titled ((Textual reading of issues in Arabic grammar)), also seeks to analyze texts for seven grammatical issues that adopted a well-known opinion or what includes its meaning according to a textual reading, and to demonstrate the ability of these issues to persuade the reader. The learner uses the argument and evidence that the grammarian brought to prove a grammatical rule, by recalling the concepts, tools and standards of textual science.     Therefore, the research methodology required starting with the concept of text in our Arabic language and how text was understood in other languages. Because it is the raw material that the study works to describe and analyze, it becomes clear that the text has a peculiarity represented by its independence, closure, and lack of reference to size, and that it is subject to several controls.     Then we move on to identifying the text analysis tools and the standards adopted by these tools. As for the seven grammatical issues that the study shed light on, they were selected from different time periods and from different grammatical books as well. To show that these standards adopted by the hadith scholars are mostly consistent to a large extent with every text written at a certain time, and that it has an impact on the reader at that time or in our time